Uji Aktivitas Antioksidan Body Butter Ekstrak Etanol Kulit Buah Naga Merah dengan Metode DPPH: Antioxidant Activity of Red Dragon Fruit Extract Body Butter Using DPPH Method - Sawiji, Repining Tiyas; La, Elisabeth Oriana Jawa (Jurnal Surya Medika (JSM), 2021)
Red dragon fruit peels (Hylocereus polyrhizus) are considered important by the community. While the red dragon fruit peel contains flavonoids, betacyanin, anthocyanin, and vitamin C which have antioxidant activity so that it can ward off free radiation and prevent cell damage. Antioxidants are molecules that can prevent the oxidation of other molecules. Antioxidants can protect the skin from various free radical cell damage. The body butter is a pharmaceutical preparation in the cosmetic field that can be used for skin health care. This study aims to determine the percentage of antioxidant activity and IC50 values in the body butter ethanol extract of red dragon fruit peels. Red dragon fruit peels were extracted first using the maceration method with 96% ethanol solvent. The antioxidant activity test was measured using UV-Vis spectrophotometry. The results showed that the antioxidant activity value of formula I obtained IC50 values (56.17 μg / mL), formula II IC50 values (88.26 μg / mL), and formula III IC50 values (146.05 μg / mL). From the results obtained, the body butter formula which has the greatest activity is the formula I (AAI = 0.7). Antioxidant activity in body butter preparations is included in the group of moderate antioxidants.